2020
DOI: 10.2147/ijn.s278189
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Peptides as an Emerging Platform for the Treatment of Metabolic Syndrome

Abstract: Metabolic syndrome comprises a cluster of comorbidities that represent a major risk of developing chronic diseases, such as type II diabetes, cardiovascular diseases, and stroke. Alarmingly, metabolic syndrome reaches epidemic proportions worldwide. Today, lifestyle changes and multiple drug-based therapies represent the gold standard to address metabolic syndrome. However, such approaches face two major limitations: complicated drug therapeutic regimes, which in most cases could lead to patient incompliance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…Peptides as novel therapeutics have been investigated across the therapeutic spectrum, but mainly in areas of high interest to the pharmaceutical industry, such as oncology [28,[44][45][46][47][48], metabolic [49][50][51][52][53][54] and cardiovascular diseases [55][56][57]. Fields, such as infectious diseases [58][59][60][61], inflammation [62][63][64], and neurodegenerative diseases [26,65,66], seem to be particularly promising.…”
Section: Therapeutic Peptides In Clinical Usementioning
confidence: 99%
“…Peptides as novel therapeutics have been investigated across the therapeutic spectrum, but mainly in areas of high interest to the pharmaceutical industry, such as oncology [28,[44][45][46][47][48], metabolic [49][50][51][52][53][54] and cardiovascular diseases [55][56][57]. Fields, such as infectious diseases [58][59][60][61], inflammation [62][63][64], and neurodegenerative diseases [26,65,66], seem to be particularly promising.…”
Section: Therapeutic Peptides In Clinical Usementioning
confidence: 99%
“…Luis Alberto Castillo-Díaz et al demonstrated that self-assembling peptide hydrogels (SAPEs) were able to form nanostructures with a diameter of 20-200 nm. The SAPEs were adjuvanted with CpG-induced and expanded antigen-specific CD8+ T cells in mice [64]. Wei Zhang discovered a novel drug nanocarrier that reduced the survival of prostate cancer cells in vitro by slowly delivering DTX (which is highly concentrated) with GRP ligands on its surface [65].…”
Section: Classes Of Drugs That Can Be Delivered By Self-assembled Pro...mentioning
confidence: 99%
“…Peptide self-assembly is a relatively new approach for creating synthetic super molecular architectures [ 12 ], which occurs via spontaneous and reversible noncovalent interactions between peptide chains [ 8 , 9 ]. The P11-4 peptide (clinically available as Curodont Repair) with the chemical structure: Ace-Gln–Gln–Arg–Phe–Glu–Trp–Glu–Phe–Glu–Gln–Gln–NH2 responds to pH triggers and assembles in the hierarchical order of tapes, ribbons, fibrils, and fibers.…”
Section: Introductionmentioning
confidence: 99%